Convenience stores as social spaces: trust and relations in deprived neighborhoods in the U.S. - Werner, Cosima (Lexington Books, 2023)
Convenience Stores as Social Spaces reveals the complexity of trust in racialized and stigmatized impoverished neighborhoods in the United States. Trust and mistrust are inherent in the atmosphere of the areas, in people's relations, and their daily practices that construe such stores are essential social spaces.